The Education of The Tahfidz Al-Qur’an in The Integrated Islamic Elementary School “Cendekia Mulia” Pondok Pesantren Al-Husna Temanggung, Central Java, Indonesia - Zainal Arifin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
The objective of this present research is on revealing the thoughts possessed by the Kyais in Pondok Pesantren Tahfidzul Quran Al Husna and on the approaches and methods adopted in this Pesantren in memorizing al-Qur’an. It is a qualitative method with the research type of phenomenology and case. The techniques of data collection were in depth interviews, observations and documentation. The data were descriptively and qualitatively analyzed and reinforced with the validity test using data triangulation. The research results are as follows. Firstyly, The education of Tahfidz al-Qur’an in pesantren tahfidzul Qur’an al husna Temanggung Central Java is based on six basic philosophies of the thoughts of the management on the education of tahfidz al-Qur’an are that memorizing al Qur’an (1) as the life capital, (2) the base of behavior, (3) the social integrity, (4) the high-quality basis o for Muslim intellectuality, (5) as the demand and need of the modern era of Islam and (6) the realization of a muslim to the al-Qur’an. Secondly, the approaches adopted in Pesantren AL Husna to facilitating the memorization of the Holy Quran are as follows: Secondly, the approaches adopted in Pesantren al Husna in facilitating the memorization of al-Qur’an are as follows: (1) taisir, starting from the easiest; (2) operational, implementing any activities that may motivate the memorization so that they are not bored with memorizing al-Qur’an; (3) psychological, fulfilling the children’s rights as individuals who are still at the level of development, and (4) tazkiyah, formulizing some tarbiyah programs that may approach the children to Allah so that they are blessed in memorizing al-Qur’an. Keywords: Al-Qur’an, Memorization, Tahfidz, Education, Pondok pesantren